Autoantibodies to the NMDA Receptor in Schizophrenia: A Literature Review - Kennedy, Liam (Trinity Student Medical Journal, 2015)
Schizophrenia is a chronic mental illness characterised by positive and negative symptoms, and cognitive dysfunction. The aetiology of the condition is poorly understood; among the various proposed hypotheses are theories involving glutamate transmission and autoimmunity. The N-methyl-D-aspartate receptor (NMDAR) is an ionotropic glutamate receptor expressed widely in the CNS, it is involved in long-term potentiation, memory and learning, and regulation of glutamatergic transmission via GABA-ergic interneurons. Pharmacological blockade of NMDARs induces positive and negative symptoms of schizophrenia in healthy subjects, and exacerbates symptoms in patients. NMDA hypo-function has been demonstrated to cause localised glutamate excito-toxicity in schizophrenia. Anti-NMDAR auto-encephalitis is a recently described neuro-immune condition, which often presents with acute psychosis. Due to the behavioural symptoms caused by the condition, 65% of those who develop anti-NMDAR auto-encephalitis are initially seen by psychiatric services. Studies of anti-NMDAR antibody prevalence in schizophrenic patients and the general population have found conflicting results. Analysis is complicated by variance between studies in terms of antibody specificity and assays used. Further work in this expanding field will help delineate the exact relevance of antibody seropositivity to the development of schizophrenia or psychosis. Anti-NMDAR auto-encephalitis represents an important aetiological factor of psychosis to be considered in the clinical assessment of acute psychosis.